PENGARUH PENGGUNAAN GAME EDUKATIF NONDIGITAL CERIBOX TERHADAP KEMAMPUAN MEMBACA INTENSIF PESERTA DIDIK KELAS IV SEKOLAH DASAR PADA MATERI SEHATLAH RAGAKU - Susanti, Susanti; Suryani, Irma; Khoirunnisa, Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the use of the non-digital educational game Ceribox on the intensive reading ability of fourth-grade students on the Sehatlah Ragaku material at SDN 98/II Muara Bungo. The study used a quantitative approach with a One Group Pretest–Posttest design and involved 20 students. Data were collected through pretests and posttests. Data analysis techniques used normality tests and hypothesis testing. The results showed an increase in intensive reading ability, marked by a higher posttest score than the pretest. Thus, the Ceribox game is proven to improve students' intensive reading ability.